O uso da maconha entre estudantes universitários e seus efeitos no controle inibitório – perspectiva neurofenomenológica - Silva Filho, Francisco Bento da (2022)
Cannabis sativa or Indian hemp, popularly marijuana, is a shrub of the Moraceae family, its medicinal, ritual or recreational use dates back thousands of years. Studies link adolescent cannabis use to socially problematic behaviors, poor academic performance, and atypical neurodevelopment. Understood as an executive function, inhibitory control has the ability to successfully inhibit inappropriate or maladaptive behavior. In relation to inhibitory control, the damages resulting from the use of Cannabis can be present in the different stages of use: insertion, dependence, maintenance, abstinence and relapse. The objective of this research, structured in three studies, was to carry out an epidemiological survey of the use of psychoactive substances by undergraduate students at UFPB, campus I, over 18 years old. The first study, epidemiological, is cross-sectional, descriptive, quantitative and observational; the ASSIST - Alcohol, Smoking and Substance Involvement Screening Test and sociodemographic questionnaire were sent online. Data were analyzed by SPSS, version 24.0. A total of 321 students participated in the research, distributed among the thirteen academic centers of UFPB. The results confirmed the prevalence of cannabis use in the list of illicit substances; pointed out the early use of the substance, there was a significant percentage of users at a time of abusive consumption and indicative of dependence, with repercussions on the quality of student performance, permanence or evasion in graduations and on the mental health of this academic segment. The scoping review, according to the study, showed that the use of Cannabis can lead to impairments in cognitive functions, with emphasis on inhibitory control depending on the dose, time of use, frequency and initial age of use. Finally, in the third study, it was found that Neurophenomenology emphasizes that the consumption of psychoactive substances is an experience that interacts with the physical body, with brain structures, affects perception and dialogues with the world in affective intonations and symbolic relationships, which are only accessible to first-person accounts, but that can dialogue with the observable states in the third person, based on embodied cognition and its instigating challenges.